Successful treatment of pulmonary embolism in a patient with polycythemia vera by rheolytic thrombectomy - Tufan Çinar; Mert İlker Hayıroğlu; Ahmet Oz (Journal of Cardiovascular and Thoracic Research, 2019)
Acute pulmonary embolism (APE) may lead to life-threatening conditions such as cardiac death and congestive heart failure. Thus, a proper diagnosis and management play a crucial role to prevent such complications. Moreover, APE is a rare clinical onset of chronic myeloproliferative disease. We herein describe a 67-year-old patient with polycythemia vera presented to our cardiology clinic with pulmonary embolism despite the fact that an intense antiplatelet treatment started secondary to acute myocardial infarction prior. Because the patient had hypotension and head trauma, rheolytic thrombectomy was performed successfully to restore adequate pulmonary perfusion.